Concha bullosa mucocele disguising as a nasal tumor in an epistaxis patient: A case report - Sigdel, Brihaspati; Pokhrel, Amrit; Paudel, Sujana (Journal of Gandaki Medical College-Nepal, 2022)
Concha bullosa is the most common anatomical variant of middle turbinate in both children and adults. When the natural drainage of concha bullosa is obstructed, it leads to the formation of mucocele. It is confusing with nasal tumor when the entire nasal cavity gets occupied. Concha bullosa mucocele and profuse epistaxis is rarely found in the same patient. Both pathologies require appropriate management for the early recovery of the patient and prevent severe complications like concha bullosa mucopyocele from concha bullosa mucocele and hypovolemic shock from profuse epistaxis. We present a 74-year-old female who presented with profuse epistaxis from the left nasal cavity due to concha bullosa mucocele filling the right nasal cavity and pushing nasal septum towards left side which was confused with nasal tumor.